Highlights in Mesoporous Silica Nanoparticles as a Multifunctional Controlled Drug Delivery Nanoplatform for Infectious Diseases Treatment - Carvalho, Gabriela Corrêa [UNESP]; Sábio, Rafael Miguel [UNESP]; de Cássia Ribeiro, Tais [UNESP]; Monteiro, Andreia Sofia [UNESP]; Pereira, Daniela Vassalo [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Chorilli, Marlus [UNESP] (Springer Nature, 2020)
Infectious diseases are a major global concern being responsible for high morbidity and mortality mainly due to the development and enhancement of multidrug-resistant microorganisms exposing the fragility of medicines and vaccines commonly used to these treatments. Taking into account the scarcity of effective formulation to treat infectious diseases, nanotechnology offers a vast possibility of ground-breaking platforms to design new treatment through smart nanostructures for drug delivery purposes. Among the available nanosystems, mesoporous silica nanoparticles (MSNs) stand out due their multifunctionality, biocompatibility and tunable properties make them emerging and actual nanocarriers for specific and controlled drug release. Considering the high demand for diseases prevention and treatment, this review exploits the MSNs fabrication and their behavior in biological media besides highlighting the most of strategies to explore the wide MSNs functionality as engineered, smart and effective controlled drug release nanovehicles for infectious diseases treatment. [Figure not available: see fulltext.].
Keywords: biological behavior; drug delivery; infectious diseases; mesoporous silica nanoparticles; multifunctional nanocarriers